URBANIZATION AND ITS EFFECTS ON BIODIVERSITY IN METROPOLITAN AREAS - Sunita Devi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In particular, biodiversity in and around cities is threatened by urbanisation, the fast growth of cities and metropolitan areas. There has been a decrease in species diversity due to habitat loss, fragmentation, and pollution brought about by the conversion of natural ecosystems into built settings brought about by the increasing concentration of human populations in metropolitan areas. the ways in which land conversion, increasing human activity, and changes in local ecosystems influence the flora and fauna of metropolitan regions, with an emphasis on the consequences of urbanisation on biodiversity. threats include invasive species, ecological process disturbance, and crucial habitat loss. Sustainable urban design, conservation initiatives, and urban green areas are all discussed in the article as potential means of lessening the toll that urbanisation takes on biodiversity. This research seeks to add to the continuing conversation on how to build cities in a way that preserves biodiversity and ecological health while simultaneously addressing the negative impacts.